2019
DOI: 10.1186/s13099-018-0281-6
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in gut microbiota associated with hepatitis B and non-hepatitis virus related hepatocellular carcinoma

Abstract: BackgroundThe onset of hepatocellular carcinoma (HCC) ranked fifth malignancies all over the world. Increasing evidences showed that the distribution of HCC was related to the incidence of chronic hepatitis B virus (HBV) infection and other factors, such as alcoholism, aflatoxin B1 ingestion and obesity. Recent studies demonstrated that gut dysbiosis plays an important role in liver diseases. However, the researches on gut microbiota of HBV and non-HBV non-HCV related HCC have not been reported. In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
139
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(163 citation statements)
references
References 59 publications
10
139
2
Order By: Relevance
“…Therefore, intestinal overgrowth of E coli may contribute to the process of hepatocarcinogenesis [106]. Recently, non-HBV/HCV-HCC patients harbored more potential pro-inflammatory bacteria (Escherichia-Shigella, Enterococcus) and reduced levels of Faecalibacterium, Ruminococcus, Ruminoclostridium which results in decrease potential of antiinflammatory short-chain fatty acids [107]. In a previous report, phylum Actinobacteria was increased in early HCC versus cirrhosis.…”
Section: Gut Microbiota and Hepatocellular Carcinomamentioning
confidence: 97%
“…Therefore, intestinal overgrowth of E coli may contribute to the process of hepatocarcinogenesis [106]. Recently, non-HBV/HCV-HCC patients harbored more potential pro-inflammatory bacteria (Escherichia-Shigella, Enterococcus) and reduced levels of Faecalibacterium, Ruminococcus, Ruminoclostridium which results in decrease potential of antiinflammatory short-chain fatty acids [107]. In a previous report, phylum Actinobacteria was increased in early HCC versus cirrhosis.…”
Section: Gut Microbiota and Hepatocellular Carcinomamentioning
confidence: 97%
“…Likewise, according to an Egyptian study, there was a high percentage of Bacteroidetes and a low percentage of Bifidobacterium in hepatitis C virus (HCV) patients [78]. Similarly, in HBV patients, there were increases in Escherichia, Shigella, and Enterococcus and decreases in Bifidobacterium, Faecalibacterium, Ruminococcus, and Ruminiclostridium [79].…”
Section: Microbiota Effects On Chronic Hepatitis B and Cmentioning
confidence: 99%
“…[38] Also, Liu et al found in his study on patients with different causes of HCC, decreased level of Faecalibacterium resulting in reduction of the level of anti-in ammatory short-chain fatty acids. [39] The family Enterobacteriaceae includes a medically important species such as Salmonella, Escherichia coli, Yersinia pestis, Klebsiella, Shigella, Proteus, Enterobacter, Serratia, and Citrobacter. Many members of this family are normally present in human as a gut microbiota.…”
Section: Variablesmentioning
confidence: 99%